2005
DOI: 10.1159/000083763
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Human Biophoton Emission

Abstract: Background: Biophoton emission is the spontaneous emission of ultraweak light emanating from all living systems, including man. The emission is linked to the endogenous production of excited states within the living system. The detection and characterisation of human biophoton emission has led to suggestions that it has potential future applications in medicine. Objectives: An overview is presented of studies on ultraweak photon emission (UPE, biophotons) from the human whole body. Methods: Electronic searches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 24 publications
(39 reference statements)
1
37
0
2
Order By: Relevance
“…Popp, Gu, and Li reported (1994) that colonies of single celled organisms adjusted their populations to a size that allows them to retain the most biophotonic light within the colony. Similarly, healthy people's cells retain more light in the form of biophotons than do the cells of unhealthy people (Popp, 2008;van Wijk & van Wijk, 2005). This is consistent with the finding that cancerous tissues emit more biophotons than do their neighboring, healthy tissues, which retain biophotons (Popp, 2009;Schamhart & van Wijk, 1987;Scholz et al, 1988).…”
Section: Meaning Makingsupporting
confidence: 53%
See 1 more Smart Citation
“…Popp, Gu, and Li reported (1994) that colonies of single celled organisms adjusted their populations to a size that allows them to retain the most biophotonic light within the colony. Similarly, healthy people's cells retain more light in the form of biophotons than do the cells of unhealthy people (Popp, 2008;van Wijk & van Wijk, 2005). This is consistent with the finding that cancerous tissues emit more biophotons than do their neighboring, healthy tissues, which retain biophotons (Popp, 2009;Schamhart & van Wijk, 1987;Scholz et al, 1988).…”
Section: Meaning Makingsupporting
confidence: 53%
“…Assessment of biophotonic activity shows promise as a diagnostic tool within the Western medical model (Brownstein et al, 2007;Ives et al, 2014), with significant differences in photon emission patterns having been found between healthy and diseased organisms (van Wijk & van Wijk, 2005). Differences in biophoton emission rates also appear between groups of healthy cells and cancer cells, with increasing emission rates correlated with increasing malignancy of tumor cells (Popp, 2009;Schamhart & van Wijk, 1987;Scholz, Staszkiewicz, Popp, & Nagl, 1988).…”
Section: International Journal Of Transpersonal Studies 137mentioning
confidence: 99%
“…This emission of bioluminescence may have significant diagnostic potential [76]. Light influences the function of all cellular processes however the absorption of light may be primarily a therapeutic principle i.e.…”
Section: The Influence Of Pathology-related Bioluminescence Upon Colomentioning
confidence: 99%
“…All the biological systems, including humans, send ultra-weak photon emission (UPE) to their surroundings [1], and spontaneous ultra-weak photon emission is generated from the relaxation of electronically excited species formed during oxidative metabolic processes [2][3][4][5].Ultra-weak photon emission is a common phenomenon and carries information about its generating processes, and closely related to photosynthesis, lipid per-oxidation, catabolism, free radical reactions, radiation effects, detoxification and carcinogenic effects, aging and death process [6]. There has been a lot of evidence that the features of UPE including intensity, spectral distribution, photon count distribution, photon spatial distribution, and photon statistical properties contain and carry information about the biological systems that result in its production [7].…”
Section: Introductionmentioning
confidence: 99%